Mental health services for German university students: acceptance of intervention targets and preference for delivery modes - Kählke, Fanny; Hasking, Penelope; Küchler, Ann-Marie; Baumeister, Harald (Frontiers in Digital Health, 2024)
Introduction: Most university students with mental disorders remain untreated. Evaluating the acceptance of intervention targets in mental health treatment, promotion, and prevention, as well as mental health service delivery modes is crucial for reducing potential barriers, increasing healthcare utilization, and efficiently allocating resources in healthcare services.The study aimed too evaluate the acceptance of various intervention targets and delivery modes of mental health care services in German first-year university students.: In total, 1,376 first-year students from two German universities from the 2017-2018 multi-center cross-sectional cohort of the StudiCare project, the German arm of the World Mental Health International College Student Survey initiative, completed a web-based survey assessing their mental health. Mental disorder status was based on self-reported data fulfilling the DSM-IV criteria. We report frequencies of accepted delivery modes (categories: group or inperson therapy with on or off campus services, self-help internet-or mobile-based intervention [IMI] with or without coaching, or a combination of a face-to-face with an IMI [blended]).. In a multinomial logistic regression, we estimated correlates of the preference for in-person vs. E-mental healthIMI vs. a combination of both modes (blended) modalities. Additionally, we reported the frequencies of intervention targets (disorder specific: e.g., social phobia, depressive mood; study-related: test anxiety, procrastination; general well-being: sleep quality, resilience), their association with mental disorders and sex, and optimal combinations of treatment targets for each mental illness.Results: German university students' acceptance is high for in-person (71%-76%), moderate for E-mental healthinternet-and mobile-based (45%-55%), and low for group delivery modes (31%-36%). In-person treatment (72%) was preferred over E-mental health IMI (19%) and blended modalities (9%). Having a mental disorder (odds ratio [OR]: 1.564), believing that digital treatments are effective (OR: 3.21), and showing no intention to use services (OR: 2.8) were associated with a preference for E-mental healthIMI compared to in-person modes. Students with prior treatment experience preferred in-person modes (OR: 0.468). In general, treatment targets acceptance was higher among female students and students with mental disorders. -> Attention! I had to include muchmore information due to the reviewer's remarks.